Agraffectomy: A Novel Technique for Treatment of Complications After Stapled Hemorrhoidopexy- A Case Study and Review of Literature - Priya Gupta; Vishakha Kalikar; Roy Patankar; Advait Patankar (World Journal of Colorectal Surgery)
Complications after stapled hemorrhoidopexy may include recurrence, severe pain, rectal stenosis, bleeding, fecal urgency, and incontinence. Furthermore, persistence of symptoms may warrant surgical intervention. A treatment modality for persistent complaints after stapled hemorrhoidopexy (SHP) is agraffectomy (removal of the retained staples), which ranges from the removal of staples through an anoscope to excision of the entire staple line with the associated scar tissue.